Fever of unknown origin: Most frequent causes in adults patients - Popovska Jovičić, Biljana; Čanović, Predrag; Gajović, Olgica; Raković, Ivana; Mijailović, Željko (Vojnosanitetski pregled, 2017)
Background/Aim. The differential diagnosis of fever of unknown origin (FUO) includes more than 200 different diseases and conditions. The aim of this study was to identify the most frequent causes of FUO among adult patients according to gender and age. Methods. The study included 74 patients examined from June 2010 to June 2013 at the Infectious Disease Clinic, Clinical Center Kragujevac in Serbia, according to the defined criteria for FUO. The patients were divided according to the diagnosis into four groups: infectious, malignant, rheumatic and “other diseases”. A cause of febricity could not be estabilshed in a portion of subjects, and they comprised the group of undiagnosed cases. Results. Infectious diseases were dominant in the study, followed by rheumatic diseases, which were most frequently found in women and the elderly. The diseases recognised as the most common causes of febricity were subacute thyroiditis, subacute endocarditis, Still’s disease, rheumatic polymyalgia with or without temporal arteritis, and cytomegalovirus infection. In 44% of the patients, the final diagnosis was composed of only six clinical entities. Conclusion. The importance of establishing the diagnosis of rheumatic disease is especially emphasised, in line with other authors’ research indicating the number of these diseases is on the rise. The diagnostic approach to FUO should always be directed to the known frequency of diseases.